Analisis Pengaruh Proses Brazing Kuningan Terhadap Perubahan Sifat Mekanis dari Pipa Baja Karbon Rendah - Mardiana Mardiana; Djoko W. Karmiadji (Forum Teknik, 2010)
Low carbon steel has suitable physical properties such as: easily to be casted, welded andmachined. Generally, this steel is used for construction, hospital and house hold equipment, andso on. Some equipment structures employ low carbon steel pipe for basic construction, in whicha lot of brazing joins are applied for connecting each pipe to form a house hold or hospitalequipment. This research analyzes the brazing methode, since it is commonly used to obtainsmoother joint surface compared with the other method and having lower melting temperaturethan the pipe. The analysis emphasizes the transformation of mechanical characteristics suchas: tensile strength, hardness, micro and macro structures. The result of this research showsthat the maximum tensile strength is 509 N/mm2 when the welded groove is 0,5 mm, or 2,35%greater than welded metal strength, and 12,5% less than base metal strength. The hardnessvalues are decreasing compared with the base metal, i.e., 18,5% of average, 18,57% at HAZ(Heat Afffected Zone), and 19,81% of pipe metal under the value of base metal.Kata kunci: Brazing, pipa baja karbon rendah, sifat mekanis